2017
DOI: 10.3329/cmoshmcj.v15i2.31804
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection in Nephrotic Syndrome: A Hospital Based Cross-Sectional Study

Abstract: Background: Urinary Tract Infection (UTI) is a common infection in nephrotic syndrome and have a propensity for long term renal damage. It may be an important cause of poor steroid response. The objective is to study the frequency and etiological organisms of urinary tract infection in idiopathic nephrotic syndrome children. Methods: This Comparative cross-sectional study was conducted in the Pediatric ward of Chittagong Medical College Hospital, Chittagong from 01.01.2009 to 31.12.2009. 52 nephrotic syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In our study regarding clinical profile of the patient it was observed that asymptomatic was 68.0% and symptomatic was 32.0% which is comparable to the study of Barua et al where 68.8% were asymptomatic 11 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study regarding clinical profile of the patient it was observed that asymptomatic was 68.0% and symptomatic was 32.0% which is comparable to the study of Barua et al where 68.8% were asymptomatic 11 .…”
Section: Discussionsupporting
confidence: 89%
“…Barua et al study observed that Male: Female ratio 1:1. In case of nephrotic syndrome without UTI (Group B), out of 36, 61.1% (n=22) were male and 38.9% (n=14) were female 11 .…”
Section: Discussionmentioning
confidence: 99%
“…was related to infections including phlegmon, peritonitis, endocarditis, meningitis, septicemia, and UTI (Cooper et al, 2005;Biswas et al, 2014;Horowitz et al, 1990). Barua et al found that nephritic syndrome patients with higher serum cholesterol were more susceptible to UTI than those with normal serum cholesterol, which might be because high cholesterol concentrations suppress lymphocyte function (Barua et al, 2016 Manuscript to be reviewed (Rochelson et al, 2007;Weglicki et al, 1992), and a previous rodent model study demonstrated that magenesium-deficiency elevated circulating levels of inflammatory cytokines (Weglicki et al, 1992). There were several limitations in our present study.Firslty,the participants were only from Zhejiang Province, China.…”
Section: Discussionmentioning
confidence: 69%
“…was related to infections including phlegmon, peritonitis, endocarditis, meningitis, septicemia and UTI (Cooper et al, 2005;Biswas, Fitchett & O'Hara, 2014;Horowitz et al, 1990). Barua et al (2017) found that nephritic syndrome patients with higher serum cholesterol were more susceptible to UTI than those with normal serum cholesterol, which might be because high cholesterol concentrations suppress lymphocyte function. With regard to magnesium, its intake had an enhancing effect on the relationship between the relative abundance of Comamonas and IL-8 concentration.…”
Section: Discussionmentioning
confidence: 99%